Analysis of Gillnet Fishery Business for Narrow-Barred Spanish Mackerel and Indo-Pacific Mackerel: Lesson Learned From KUB Kampung Baru in Muara Kintap, Indonesia - AHMADI AHMADI (Asian Fisheries Science)
This study sheds light on the business sustainability of the gillnet fishery for narrow-barred Spanish mackerel (Scomberomorus commerson) and Indo-Pacific mackerel (Scomberomorus guttatus), locally called "Tenggiri" and "Kembung," respectively, undertaken by the Kelompok Usaha Bersama (KUB) Kampung Baru, a collective business group in Muara Kintap, Indonesia. Employing a descriptive approach, we analyse the fisher group's financial performance, profitability, marketing channels, gap and challenges. Key findings reveal a thriving operation. Over 327 tons of fresh and dried mackerel were procured across 216 fishing trips involving 18 vessels. Fish prices varied along the supply chain, with producers earning USD1–7 kg-1 and wholesalers fetching USD2–8 kg-1. This fisher group generated a substantial annual profit of USD488,346 year-1, translating to roughly USD43,882 vessel-1 year-1. Strong financial indicators further reinforce this success. A healthy return on investment (R/C ratio of 1.48) and a rapid payback period (0.63 years) demonstrate viability. Positive net present value (NPV) of USD1,417,004, net benefit-cost ratio (NetBCR) exceeding 1 (6.91), and an impressive internal rate of return (IRR) of 159 % confirm financial feasibility. Vessel owners enjoyed a substantial monthly income of USD2,438 trip-1 vessel-1, significantly exceeding the provincial minimum wage of USD172 month-1. The producer-wholesaler-consumer marketing channel functioned efficiently, with margins ranging from 9 to 40 % and fishers retaining a significant share (60–91 %). These findings also highlight the underexploited potential of the mackerel fishery to bolster fishery processing businesses. The fisher group’s success story exemplifies the potential for good profit margins, swift returns on investment, and the establishment of sustainable practices within the industry.